Reviewing the art of aeromagnetic data interpretation in geophysical surveys. - Kiani, Innocent; Okosiemiema, Raphael (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
The study delves into the theory, application, and interpretation of aeromagnetic surveys, drawing insights from foundational publications in the field. Emphasizing the significance of aeromagnetic data in mapping magnetic anomalies, the paper discusses advancements such as computer-aided depth estimation and their applications in environmental evaluations and mineral exploration. The review underscores the challenges inherent in interpreting aeromagnetic data, acknowledging the complexities and ongoing efforts in achieving accurate and efficient data interpretation in geophysical surveying. A detailed overview of various geophysical survey techniques, including seismic surveys, electromagnetic surveys, ground-penetrating radar, and gravity surveys, set the stage for a focused examination of aeromagnetic surveys as a versatile geophysical tool. Aeromagnetic surveys, conducted from aerial platforms, have gained prominence in geologic mapping, environmental studies, and mineral exploration due to their high spatial resolution and cost-effectiveness. The subsequent section explores the characteristics and applications of aeromagnetic maps, emphasizing their role in identifying magnetic anomalies and offering insights into subsurface geological structures. The article also delves into data interpretation techniques, discussing the preparation and enhancement of raw magnetic data and analytical methods for locating and describing magnetic anomalies. Real-world case studies illustrate the practical applications of aeromagnetic data interpretation in mineral exploration, environmental studies, and geological mapping. The versatility of aeromagnetic data interpretation is showcased through applications in mineral exploration, environmental monitoring, geological structure mapping, and archaeological surveys. Future directions anticipate further integration with diverse geophysical datasets, advancements in inversion techniques, enhanced 3D visualization, increased automation, and continued interdisciplinary cooperation. In conclusion, the article emphasizes the indispensable role of aeromagnetic data interpretation in geophysical surveying, contributing to our understanding of the Earth's magnetic properties, geological formations, and vital resources. The dynamic nature of the field, marked by ongoing advancements and interdisciplinary collaboration, positions aeromagnetic data interpretation as a cornerstone in the quest for knowledge about the Earth's subsurface.